2021
DOI: 10.3389/fsurg.2020.588215
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Laparoscopic Living Donor Nephrectomy: The University of Florence Technique

Abstract: Objective: To provide a step-by-step overview of the University of Florence technique for robotic living donor nephrectomy (LDN), focusing on its technical nuances and perioperative outcomes.Methods: A dedicated robotic LDN program at our Institution was codified in 2012. Data from patients undergoing robotic LDN from 2012 to 2019 were prospectively collected. All robotic LDNs were performed by a highly experienced surgeon, using the da Vinci Si robotic platform in a three-arm configuration. In this report we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…There are different minimally invasive techniques, including standard pure laparoscopic, hand-assisted laparoscopic, hand-assisted retroperitoneoscopic, pure retroperitoneoscopic, and robotic-assisted live donor nephrectomy [15,16]. Of note, while LDN has become a common practice in most transplant centers around the world due to the benefits that it provides for the donor, the use of robotic-assisted LDN might further improve the outcomes of the procedure, providing distinct benefits, not only for the donor, but also for the surgeon, based on the enhanced dexterity, ergonomic and subsequent confidence of the surgeon that allow for a more standardized and potentially easier procedure, compared to standard laparoscopy, especially in difficult donors with high BMI or complex vascular anatomy [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different minimally invasive techniques, including standard pure laparoscopic, hand-assisted laparoscopic, hand-assisted retroperitoneoscopic, pure retroperitoneoscopic, and robotic-assisted live donor nephrectomy [15,16]. Of note, while LDN has become a common practice in most transplant centers around the world due to the benefits that it provides for the donor, the use of robotic-assisted LDN might further improve the outcomes of the procedure, providing distinct benefits, not only for the donor, but also for the surgeon, based on the enhanced dexterity, ergonomic and subsequent confidence of the surgeon that allow for a more standardized and potentially easier procedure, compared to standard laparoscopy, especially in difficult donors with high BMI or complex vascular anatomy [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the state-of-the-art indications and techniques/approaches for living donor nephrectomy, the current European Association of Urology (EAU) guidelines on renal transplantation consider LDN as the preferred technique, due to the highly valid evidence confirming its equality to open surgery in terms of patient and graft survival, graft function, urological complications and rejection rates [7]. Moreover, robotic-assisted living donor nephrectomy (RLDN) represents a safe technique and offers a reasonable alternative to conventional laparoscopic surgery in living kidney donation, aiming in maximizing donor safety, minimizing donor discomfort and improving surgeon's ergonomics and confidence [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We consider laparoscopic donor nephrectomy to be one of the most complex operations; moreover, in this procedure, healthy donors with altruistic motivations are subjected to surgical interventions and risks without any expected therapeutic effects. Other recent studies have shown the advantages of robotic laparoscopic donor nephrectomy over traditional 2D laparoscopic donor nephrectomy [ 24 , 25 ]. At the same time, Mulder et al [ 8 ], in a series of 40 operations, showed clinical and economic benefits of using 3D laparoscopic donor nephrectomy before robotic nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is essential to emphasize that the holy grail of “steps and technique of reduction” remains an art more than a science, and the extensive open surgery was reportedly associated with a high risk of neurovascular injury leading to poor prognosis. With the rapid development of technology in the 21st century, robot techniques have become a powerful tool and an emerging art assisting surgeons to eliminate all kinds of complex barricades [ 4 , 5 ]. Some have been prevailing in PF fixation [ 6 , 7 , 8 ], but few have been introduced to handle the issue of PF reduction, which is both a highly skilled and physically demanding procedure, and often time-consuming.…”
Section: Introductionmentioning
confidence: 99%